Engineering physics - Bhattacharya, D. K.; Tandon, Poonam (Oxford University Press, 2015)
Engineering Physics is primarily designed to serve as a textbook for undergraduate students of engineering. It will also serve as a reference book for undergraduate science (B Sc) students, scientists, technologists, and practitioners of various branches of engineering. The book thoroughlyexplains all relevant and important topics in an easy-to-understand manner. Beginning with a detailed discussion on optics, the book goes on to discuss waves and oscillations, architectural acoustics, and ultrasonics in Part I. The basic principles of classical mechanics, relativistic mechanics, quantum mechanics, and statistical mechanics are included under Part II. Electromagnetism-related topics, namely dielectric properties, magnetic properties, and electromagnetic field theory are explained under Part III. Part IV provides an in-depth treatment of topics such as X-rays, crystal physics, band theory of solids, and semiconductor physics. It also coversconducting and superconducting materials. Topics such as nuclear physics, radioactivity, and new engineering materials and nanotechnology are presented in the last section of the book. The text also contains useful appendices on SI units, important physical and lattice constants, periodic table, andproperties of semiconductors and relevant compounds for ready reference. Plenty of solved examples, well-labelled illustrations and chapter-end exercises are provided in every chapter for better understanding of the concepts and their applications.